Novel mass spectrometry‐based comprehensive lipidomic analysis of plasma from patients with inflammatory bowel disease. Issue 8 (23rd April 2020) - Iwatani, Shuko; Iijima, Hideki; Otake, Yuriko; Amano, Takahiro; Tani, Mizuki; Yoshihara, Takeo; Tashiro, Taku; Tsujii, Yoshiki; Inoue, Takahiro; Hayashi, Yoshito; Takeda, Kiyoshi; Hayashi, Akio; et al.
Abstract: Background and Aim: Lipids play important roles in inflammation and may be involved in the pathophysiology of inflammatory bowel disease (IBD). Here, we evaluated the characteristics of the plasma lipid profile in patients with IBD. Methods: Plasma samples were collected from 20 patients with Crohn's disease (CD), 20 patients with ulcerative colitis (UC), and 10 healthy volunteers (HVs) after overnight fasting. The subjects were men between 20 and 49 years of age with no history of hyperlipidemia. A total of 698 molecular species in 22 lipid classes were analyzed by ultra‐performance liquid chromatography‐electrospray ionization‐tandem mass spectrometry. Results: Lipid classes of lysophosphatidic acid, lysophosphatidylserine (LPS), phosphatidylserine (PS), and shingosine‐1‐phosphate (S1P) were significantly increased in UC patients compared with the HV. The LPS, PS, and S1P levels were significantly increased, while those of lysophosphatidylinositol and phosphatidylcholine were significantly decreased in CD patients compared with HV. Among PS species, the levels of PSacyl (PSa) 40:3, PSa 38:3, and PSa 42:4 were significantly higher in CD patients, both active and remissive stage, than in HV. The LPS 18:0 level was significantly higher in CD and UC patients compared with HV. PSa 40:3 and PSa 38:3 levels positively correlated with the Crohn's Disease Activity Index, erythrocyte sedimentation rate, and platelet count and negatively correlated with hemoglobin, hematocrit, and albumin levels in CD patients. Conclusion: The lipid profile in IBD patients exhibits significant alterations, and PS levels are associated with clinical disease activity in CD patients.